PERAN GURU DAN STRATEGI DALAM MENINGKATKAN PARTISIPASI SISWA - Khairun Nissa; Jihan Hidayah Putri (Jurnal Guru Kita PGSD, 2021)
Abstract: Teacher’s Role and Strategies in Enhancing Students’ Active Participation. Pupils’ active engagement in the classroom is important as implementing student-centered learning and increase students’ critical thinking. Dornyei (2007) claimed that the teacher is one of the factors that can influence students’ willingness to communicate. This study aimed to investigate teachers’ role and strategies in enhancing EFL learners’ tendency to talk. The researcher started to explore teacher’s contribution in supporting students’ self-confidence and effective strategies that could be applied in the classroom. This research used literature research methodology to explore the roles and approaches. The findings showed that the roles of the educators are as facilitator, and teacher’s attitude such as teacher’s wait time and techniques in delivering the message, influence students’ participation significantly during the learning process. Also, there are three techniques to reduce students’ reticence namely teacher-fronted strategy, facilitator-oriented strategy, and learner-oriented strategy. Finally, some suggestions have been remarked in the last chapter of this research. Keywords: Teacher’s role, Strategies, Active learners, participation Abstrak: Peran Guru dan Strategi Meningkatkan Partisipasi Siswa. Peran aktif siswa dikelas sangat penting dalam mengaplikasikan pembelajaran berbasis siswa dan juga untuk meningkatkan kemampuan berfikir kritis. Dornyei (2007) menyatakan bahwa guru adalah salah satu faktor yang dapat mempengaruhi keinginan siswa untuk berbicara dikelas. Penelitian ini bertujuan untuk menelaah peran serta strategi yang dapat dilakukan untuk meningkatkan partisipasi siswa. Kontribusi guru dalam menumbuhkan motivasi siswa serta strategi yang efektif untuk mengatasi permasalahan siswa akan dibahas secara terperinci. Metode yang digunakan dalam meneliti kedua komponen tersebut adalah studi literatur. Hasil penelitian menunjukkan bahwa terdapat tiga peran penting guru, yaitu guru sebagai fasilitator, penggunaan waktu tunggu dikelas oleh guru dan juga teknik dalam penyampaian umpan balik. Juga, terdapat tiga strategi yang dapat digunakan yaitu strategi teacher’fronted, facilitator oriented dan juga learner oriented. Selain itu, saran untuk meningkatkan motivasi siswa berbicara dikelas akan diuraikan pada bagian akhir penelitian ini. Kata Kunci: Peran Guru, Strategi, Siswa, partisipasi